PRONOMINA DALAM LANGGAM KATO NAN AMPEK DALAM KABA KLASIK MINANGKABAU - Nauri, Silvio Wynne; Agustina, Agustina; Juita, Novia (Universitas Negeri Padang, 2018)
The purpose of this research is to describe: (1) the kind of persona pronoun in langgam kato nan ampek on kaba klasik Minangkabau; (2) the function of persona pronoun usage in langgam kato nan ampek on kaba klasik Minangkabau. The kind of this research is qualitative research using descriptive method. This research data is the sentences which contain persona pronoun element in langgam kato nan ampek on kaba klasik Minangkabau. The sources of this research are kaba si buyuang karuik, sabai nan aluih, putri nilam cayo, and kaba sutan lembah tuah. This research have been collect in the following way: 1. Clarify according with the purpose of the research 2. Analyze and interpret data based on the theory usage; 3. Conclude the data and 4. Make research report. The result of this research is. first, found three types of persona pronomina in langgam kato nan ampek on kaba klasik Minangkabau, that is 1. first person(single) den/aden, ambo, denai and first person (plural) kami,awak,kito; 2. Second person (single) kau/wakau,ang/waang and second person (plural) kalian,wakkalian; and 3. Third person (single) nyo/inyo, baliau. Second, found four function of persona pronoun in langgam kato nan ampek on kaba klasik Minangkabau, that is: 1. Kato mandaki 2. Kato manurun 3. Kato malereang and 4. Kato mandata which are kinship and non kinship.Â Â Keywords: Type, Function, Kaba Classic Minangkabau